Report of a series of cases of iatrogenic diseases treated in an emergency room of a public teaching hospital in western Paraná due to unsuccessful outpatient dental surgeries (Research, Society and Development, 2024)
Introduction: Clinical surgical procedures are frequent in dental offices and should be performed with caution and responsibility since hemorrhages, hematomas, lesions in adjacent soft tissues, bone fractures, infections, and impairment of important anatomical structures may occur during these procedures. Objective: To analyze and report seven clinical cases in which iatrogenic events occurred and were treated at the University Hospital of Western Paraná (HUOP). In both cases, complications occurred due to failures in the execution of clinical procedures by dental surgeons. Case reports: The cases addressed in the present study are mandibular fractures resulting from extraction of the third molar and removal of the lower protocol for hygiene, postoperative hemorrhage caused by failure in the anamnesis and in the request for complementary tests, abscesses of odontogenic origin and a foreign body in the maxillary sinus after a simple extraction attempt. In all cases, it was possible to observe errors, either due to lack of prior planning, non-execution of a good clinical examination or insufficient execution of technique. Conclusion: The professional is responsible for properly planning the cases and executing them in order to ensure the patient's safety.